Application of Health Promotion Model: Analysis Factors Associated with Physical Activity in Prehypertension Adults - Dini Tryastuti; Meliana Sari; Andini Nursyifa Tresna; Fuad Almubarok (GLOBAL HEALTH SCIENCE GROUP, 2025)
The 2018 Basic Health Research (Riskesdas), showed that 33.5% of Indonesian adolescents and adults engage in a sedentary lifestyle, marked by insufficient physical activity. A lack of physical activity can lead to health risks, especially complications related to non-communicable diseases. This study aims to determine the relationship between physical activity and its determinants among adults with prehypertension. This study used a quantitative approach with a cross-sectional study design. A total of 262 adults with prehypertension in Ciputat Timur participated in the study, The sampling technique used was purposive sampling. Data were collected using self-administered questionnaires. Data analysis was conducted using the chi-square test to examine the relationship between physical activity and its determinants, and logistic regression to identify predictors of physical activity. The study found that 64.6% of respondents had low physical activity levels. There was a significant relationship between physical activity and factors such as gender, perceived benefits, perceived barriers, self-efficacy, and social support. In conclusion, social support was identified as the most significant determinant of physical activity among adults with prehypertension. These findings may contribute to the development of interventions and strategies aimed at promoting physical activity participation among adults.